Gerakan anti korupsi melalui nilai keislaman - aufa, shabrina aulia (Maliki Interdisciplinary Journal, 2026)
The anti-corruption movement for Indonesia’s future is a strategic effort that relies not only on law enforcement but also on character building and public moral awareness. One important approach is through anti-corruption education based on ethical and religious values. This education plays a role in instilling honesty, responsibility, discipline, and concern for the common good from an early age, particularly in educational settings.The implementation of anti-corruption education can be achieved through the integration of these values ​​into the learning process and through instilling them in daily life. Educational environments, both schools and universities, play a crucial role as spaces for character formation that foster a generation of integrity. Furthermore, support from families and communities is also crucial in strengthening an anti-corruption culture.Thus, the anti-corruption movement is not only the responsibility of the government, but also of all elements of society. Through sustainable, values-based education, it is hoped that a future generation of Indonesians will emerge with high integrity and be able to reject all forms of corruption.